Temporary dietary fiber depletion prompts rapid and lasting gut microbiota restructuring in mice - Colombe Rous; Julie Cadiou; Hiba Yazbek; Elena Monzel; Mahesh S. Desai; Joel Doré; Maarten van de Guchte; Stanislas Mondot (Microbiology Spectrum)
ABSTRACT Long-term alterations of the gut microbiota and host symbiosis after a dietary perturbation remain insufficiently understood and characterized. In this study, we investigate the impact of temporary dietary fiber depletion in mice that received a diet with reduced fiber content (RFD) for 3 weeks followed by a return to a standard chow diet for 6 weeks, compared to mice that only received a chow diet. Fiber deprivation was accompanied by a reduction of microbiota diversity and an increase in mucolytic and sulfate-reducing bacteria. The activities of enzymes targeting glycans from the host mucus were increased accordingly, while those targeting plant fibers were decreased. On the host side, we report transiently higher quantities of host DNA in feces during the RFD suggesting an impaired gut barrier function. Six weeks after the return to the chow diet, lasting changes in microbiota composition were observed, as exemplified by the replacement of durably depleted amplicon sequence variants close to Duncaniella dubosii by other members of the Muribaculaceae family. The observation of two distinct gut microbial communities in mice under identical environmental and alimentary conditions at the end of the experiment suggests the existence of alternative stable microbiota states.IMPORTANCEIn this article, the authors explore the impact of a diet with reduced fiber content on the gut microbiota-host symbiosis in a mouse model. More importantly, they examine the resilience of the intestinal symbiosis after the return to a standard (chow) diet. Some of the measured parameters (intestinal barrier impairment and bacterial glycan-degrading enzymatic activities) returned to control values. However, this was not the case for bacterial richness—the number of different bacteria observed—which remained durably reduced. Among related bacteria, some groups receded and remained undetected until 6 weeks after the return to the chow diet while others saw their abundance increase in replacement. The authors find that a temporary fiber deprivation lasting as little as 3 weeks can cause a transition to an alternative stable microbiota state, i.e., a lasting change in intestinal microbiota composition.